Passive Seismic Ambient Noise Surface Wave Tomography Applied to Two Exploration Targets in Ontario, Canada. Issue 1 (1st December 2019) - Lynch, Richard; Hollis, Dan; McBride, John; Arndt, Nick; Brenguier, Florent; Mordret, Aurélien; Boué, Pierre; Beaupretre, Sophie; Santaguida, Frank; Chisolm, Dan
Summary: As mineral exploration seeks deeper targets and targets under cover, the need for low cost and low impact subsurface imaging is increasingly important. A recent addition to the toolbox of geophysical methods is ambient noise surface wave tomography (ANSWT) which produces an S-wave velocity image of the subsurface using naturally occurring seismic signals from waves, oceans, trains, etc. - no active controlled seismic sources required. In this presentation, we provide a brief introduction of the ANSWT method and review two recent projects: Marathon Phase III and Schumann Lake, both projects located in Ontario, Canada.